2019
DOI: 10.1016/j.compositesb.2019.05.054
|View full text |Cite
|
Sign up to set email alerts
|

Effective antimicrobial materials based on low-density polyethylene (LDPE) with zinc oxide (ZnO) nanoparticles

Abstract: La versión de editor/PDF no puede utilizarse. Debe enlazar a la versión de editor con DOI. Author's post-print must be released with a Creative Commons Attribution Non-Commercial No Derivatives License.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
67
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 24 publications
6
67
0
1
Order By: Relevance
“…The amorphous layers near the surface can accommodate more water molecules, resulting in a greater release of active agent. A similar behavior was obtained from the silver and zinc oxide nanoparticles [8,10]. The active agent release from LDPE + β-CD+active compound increased slowly during the first weeks (1-6) due to the slow migration of active agent through the β-CD and the amorphous part of the specimen films.…”
Section: Active Agent Releasesupporting
confidence: 69%
See 1 more Smart Citation
“…The amorphous layers near the surface can accommodate more water molecules, resulting in a greater release of active agent. A similar behavior was obtained from the silver and zinc oxide nanoparticles [8,10]. The active agent release from LDPE + β-CD+active compound increased slowly during the first weeks (1-6) due to the slow migration of active agent through the β-CD and the amorphous part of the specimen films.…”
Section: Active Agent Releasesupporting
confidence: 69%
“…Several studies have been reported based on polyethylene as a matrix with the incorporation of organic and inorganic nanoparticles as active agents. The preparation of nanocomposites based on polyethylene (PE) with the incorporation of nanoparticles such as silver (10 nm, 5 wt %) [8], copper (10-40 nm, 5 wt %), TiO 2 [9], or ZnO [10] has been reported. The nanocomposites with silver and copper incorporation show biocidal activity close to 99.9% against Escherichia coli [11], but these nanoparticles have some disadvantages that have not been reported, such as innocuity and toxicity in humans.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms can be based on either catalytic biocidal activities or the release of some active agents from the nanoparticles. Examples of antimicrobial nanoparticles used as fillers are silver [ 8 ]; copper [ 9 ]; and, recently, TiO 2 and ZnO nanoparticles [ 10 , 11 ], which have been incorporated into polyolefins such as polyethylene. From the different polymer matrices, polyolefins such as polyethylene are highlighted due to their broad range of applications in packaging and medicines [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…When the melt-mixing method was used, the elongation at break decreased 10% with 1.5 wt.% ZnO. 18 In LDPE/ZnO nanocomposites obtained by melt compounding, 17 the Young's modulus increase was of 9% for an incorporation of ZnO of 3%, also inferior to the one obtained by in situ polymerization for the same amount of particles incorporation.…”
Section: Resultsmentioning
confidence: 97%
“…LDPE/ZnO composites with mean particle sizes on the order of 770 nm showed antimicrobial activity against Escherichia coli and Staphylococcus aureus. 7 Recently, Zapata and co-workers 17 obtained LDPE/ZnO and LDPE/ZnO modified with oleic acid by melt compounding. The nanocomposites showed increase of Young's modulus and antimicrobial properties against Escherichia coli.…”
Section: Introductionmentioning
confidence: 99%